Electrostatically charged porous nonwoven webs, films and masks obtained therefrom, and methods of making and cleaning
The preparation of fluoropolymer porous fiber webs through electrospinning technology solves the problem of low efficiency of existing air filtration devices when filtering nano and submicron aerosols, and uses low toxic solvents to achieve efficient and safe air filtration effects.
Patent Information
- Application Number
- CN202180050987.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-06-19
- Filing Date
- 2021-06-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-06-17
AI Technical Summary
Existing air filtration devices are inefficient in filtering nano and submicron aerosols, and the toxic solvents used pose a potential health and safety threat.
Using a porous fiber web based on fluoropolymers, prepared by electrospinning technology, the fibers contain at least 65% of the beta-phase crystallinity to improve the electrostatic efficiency and use low-toxic or non-toxic solvents.
The filtration efficiency of the air filtration device to nano and submicron aerosols is improved, the pressure drop is reduced, and the materials used are health-safe and harmless, and are stable during the washing and sterilization process.
Smart Images

Figure CN115885067B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of porous webs (webs) based on one or more fluoropolymers and membranes obtained therefrom.
[0002] In particular, the present invention relates to such webs for filtering nano and / or submicron aerosols, the webs comprising a population of fluoropolymer based fibers.
[0003] The invention also relates to the use of such a web or a membrane obtained therefrom in an air filtration device, in particular in a respiratory protection filter apparatus.
[0004] The invention also relates to methods for realizing these webs and / or these films.
[0005] The invention finally relates to a method for cleaning these webs and / or these films. Prior art
[0006] In the context of the health crisis associated with the coronavirus Covid-19, it has proven to be particularly important to develop and produce air filtering devices, in particular respiratory protection filtering devices (medical masks, FFP-type masks, cartridge masks with or without assisted ventilation) or other devices intended for air filtration, which are more efficient, effective, durable and guarantee good safety and good health for the user. In the case of respiratory protection filtering devices, it has also proven to be important that the latter are sufficiently comfortable for their users ("good breathability") and reusable.
[0007] A key element of air filtration devices, in particular respiratory protection filtration devices, is the presence of one or more porous membranes consisting of nonwoven fibers. These membranes ensure the blocking of potentially harmful aerosols containing small-sized particles, such as bacteria or even viruses.
[0008] Several methods of producing such membranes are known, with or without the nonwoven fibers being deposited on a porous substrate. In particular, methods starting with polymer membranes (e.g., membrane grinding or carding), via blowing molten polymers (e.g., meltblowing), or polymers in solutions (e.g., solution electrospinning) are known (see: Irwin M. Hutten, Handbook of Nonwoven Filter Media (Second Edition)).
[0009] These methods can be combined with methods which make it possible to electrostatically charge the nonwoven by plasma treatment and in particular by direct current corona treatment, by friction (triboelectric effect), by wet steam or also by dry steam.
[0010] A membrane with fibers whose surface is electrostatically charged will be able to block polluting or infectious elements by the electrostatic effect and thus improve the filtration efficiency compared to an uncharged membrane.
[0011] The membranes are usually composed of synthetic fibers or a combination of synthetic fibers obtained from thermoplastic polymers such as, but not limited to, polyolefins, polyamides, polyethylenes, polyimides, polyacrylates, polymethacrylates, polyurethanes or also fluoropolymers, and in particular polyvinylidene fluoride. The most widely used polymers to date are polyolefins, and in particular polypropylene.
[0012] Generally, three main physical mechanisms are singled out, whereby the filter element makes it possible to restrict the passage of aerosols carried by the air flow. Two involve mechanical effects and the third involves electrostatic effects. The first effect, "impact", is observed when the size of the particles is close to that of the pores and is therefore blocked by the impact of the fibers.
[0013] The second effect, "diffusion", is related to the fact that scattering particles have a Brownian component in their motion and therefore tend to come into contact with the fibers and adhere to them. This mechanism makes it possible to prevent the passage of particles whose size is smaller than the hole size.
[0014] The third effect, "induction", is associated with electrostatic phenomena. If the particles to be filtered are charged or polarizable, they tend to be attracted to the fibers, which themselves have a charge or dipole. This third effect makes it possible to limit the passage of particles whose size is significantly smaller than the pore size. This becomes more pronounced as the fiber diameter decreases.
[0015] Furthermore, to evaluate the performance quality of a membrane, several criteria are usually used, and in particular: efficiency, pressure drop and quality factor.
[0016] The efficiency η(t) is the ability of the membrane to block harmful aerosols. It is evaluated by the difference in the concentration of pollutants upstream and downstream of the filter element according to the following formula:
[0017] [Mathematical formula 1]
[0018]
[0019] Among them C in and C out It is the concentration of pollutants that is specifically determined to have to be filtered upstream or downstream of the filter element.
[0020] The characteristics of the particular contaminant of interest are usually defined by the upper range of the size of the particles that it is desired to remove.
[0021] The goal is generally maximum efficiency with as little degradation as possible over time, temperature, humidity variations in a more or less aggressive environment, or during treatment, decontamination and / or regeneration phases of the membrane.
[0022] The efficiency η(t) can be expressed in terms of two components as follows:
[0023] [Mathematical formula 2]
[0024] η(t)=η.(m(t)+e(t)),
[0025] where m(t) is the component associated with the mechanical effect, and e(t) is the component associated with the electrostatic effect.
[0026] It should be readily appreciated that as the characteristic dimensions of the pores decrease, the mechanical component of the efficiency increases, and therefore the efficiency of the filter element also increases.
[0027] The pressure drop ΔP is the pressure difference between the upstream and downstream of the filter element through which the gas flow containing or not containing the pollutant elements passes. Therefore, it characterizes the ability of the gas (such as air) to pass through the filter element. In general, the goal is to have the lowest possible pressure drop without assisted ventilation, especially for the filter element entering the respiratory protection filter device, because too large a pressure drop makes it difficult to breathe through the mask without assistance.
[0028] Thus, it is generally undesirable to excessively reduce the characteristic size of the pores and / or the porosity so as not to excessively increase the pressure drop across the filter element.
[0029] Quality factor Q f (t) is defined by the following formula:
[0030] [Mathematical formula 3]
[0031]
[0032] where η(t) and ΔP are the efficiency and pressure drop respectively as defined above.
[0033] The quality factor allows the overall performance quality and the possibility of using a filter to be evaluated by balancing its effectiveness in filtering particles of a given size and its pressure drop so that it can allow airflow (and in particular inspired air or exhaled carbon dioxide) to circulate.
[0034] It goes without saying that the quality factor depends on the optimization of the characteristic size of the pores, the porosity (the volume of the filter element not filled with fibers) and the electrostatic efficiency. The goal is to improve the efficiency by having pores that are small enough to block polluting or infectious particles but large enough to make low pressure drop possible. The goal is also to maximize the electrostatic effect, which makes it possible to increase the size of the pores while making high efficiency possible, and to minimize the diameter of the fibers so that small pores can be formed while maintaining high porosity. This compromise is more difficult to achieve when the particles desired to be filtered are of small size. This is especially true for the filtration of viruses with characteristic sizes of the order of 100nm or hundreds of nanometers.
[0035] The method that is particularly suitable for producing porous nonwoven membranes that resist viruses is a method for electrostatic spinning of polymers in solution. In this method, a solution containing a formulation of a polymer and an additive in a formulation of a suitable solvent is forced to pass through a narrow needle die or nozzle. The die reaches a high potential (positive or negative), typically in the order of thousands of volts or tens of thousands of kilovolts. When the solution is sufficiently polar and / or conductive, the static charge generated by the electric field in the solution will compensate for surface tension, forcing the fluid droplet to stretch. Due to the almost complete (actually even complete) evaporation of the solvent, solid fibers will form and be deposited on a collector connected to electrical grounding. The fiber group can therefore form a porous nonwoven membrane. This method makes it possible to produce fibers of variable size, and particularly the order of magnitude of diameter is tens or hundreds of nanometers of fibers, which the method cannot do as conventional fusion methods.
[0036] It is known in the prior art (for example in US2019 / 0314746) that a porous nonwoven PVDF web is obtained by an electrospinning method suitable for air filtration. More specifically, US2019 / 0314746 describes a method for electrospinning a PVDF solution at a voltage of 20 kV, wherein the PVDF used has a molecular weight of 530 000 and is in a mixture of a DMF / acetone solvent in a ratio of 8 / 2 (v / v) at 20% w / v (weight / volume). The nanofibers are electrospun onto the surface of a drum covered with a nonwoven polypropylene (PP) substrate. Once the electrospinning of the nanofibers is completed, the film formed by the PVDF web on its PP substrate is dried in a vacuum oven at 40 ° C to remove as much residual solvent as possible. The dried film is then corona polarized to fully charge the electret. The PVDF fiber group in the film has a diameter distribution with a median diameter of 450 nm.
[0037] Solution electrospinning makes it possible, under certain conditions, to obtain fibers with diameters small enough to make good air permeability and good mechanical filtration efficiency for membranes used for air filtration. Poly(vinylidene fluoride), more commonly known as PVDF, makes it possible to obtain hydrophobic and chemically resistant membranes. PVDF is a semicrystalline thermoplastic polymer that exhibits polymorphism, i.e., it can crystallize in different crystalline phases: α, β, γ and δ. The sequence of trans (T) or gauche (non-planar) (G) conformations along the chains and the arrangement of the chains between themselves in the crystal (symmetry) define the phase and its polar or non-polar nature.
[0038] The α phase can be The phase is described by a sequence of (trans-twisted + trans-twisted-) conformations. This is the only nonpolar phase.
[0039] The beta phase can be described by a sequence of individual "trans" (T) conformations along the chain, which themselves are arranged in a non-centrosymmetric orthorhombic unit cell. The beta phase is the most polar phase.
[0040] There are intermediates between the α phase and the β phase, especially the γ phase, which can be The δ phase is also polar but has only been studied to a lesser extent.
[0041] Polar phases (especially the most polar β phase) exhibit important ferroelectric properties. This means that the material is subjected to a force greater than a characteristic field (called the coercive field (E c )) The application of an electric field at a value of )) makes it possible to orient the dipoles formed by the C-F bonds in the same direction. Due to the ferroelectric properties, this dipole orientation, which is sufficiently stable over time, gives the material a residual polarization strength at zero electric field. Therefore, the presence of the β phase in PVDF fibers is particularly advantageous for air filtration applications, because it makes it possible to generate charges bonded to the material and thus increase the electrostatic efficiency (which is greater than that of fibers of non-ferroelectric dielectric materials).
[0042] Electrospinning of a solution of PVDF in dimethylformamide (DMF) is known by Andrew et al. (see: Effect of electrospinning on the ferroelectric phase content of polyvinylidene difluoride fibers, Langmuir, 2008, Vol. 24, No. 3, pp. 670-672). By varying certain parameters of the method (in the appropriate case of the concentration of PVDF in the solution and the voltage applied during electrospinning), the authors managed to obtain a web of PVDF fibers having a crystallinity of 49% to 58%, with a percentage of β phase in the crystalline phase of up to 75%. Thus, the fibers obtained have a β phase content of 37% to 47% by weight relative to the weight of the fiber.
[0043] The electrospinning of a PVDF solution with a concentration of 20% by weight in DMF was known by Baqueri et al. (see: Influence of processing conditions on polymorphic behavior, crystallinity, and morphology of electrospun poly (vinylidenefluoride) nanofibers, Journal of Applied Polymer Science, 2015, Vol. 132, No. 30). The authors managed to obtain a web of PVDF fibers with a crystallinity of 53% at an electrospinning flow rate of 0.5 ml / h and a voltage applied during electrospinning of 13 kV, and the percentage of β phase in the crystalline phase was up to 83%. Therefore, the obtained fibers have a β phase content of 44% by weight relative to the weight of the fibers. In addition, their median diameter is 55 nm.
[0044] It would be desirable to provide a web having fibers in the beta phase in a larger proportion relative to the weight of the fibers in order to improve the ferroelectric properties of the web.
[0045] In addition, due to the limited solubility of PVDF in a small amount of usually very toxic solvents (such as DMF), the implementation of the method for electrospinning PVDF fibers in solution may be quite cumbersome due to the need to handle a large amount of these solvents. In addition, it should not be overlooked that in some cases, at least and to some extent, these solvents may still be impregnated in the PVDF fibers. Especially if the membrane is used to manufacture respiratory protection filtering equipment, this brings potential health and safety problems to the user. Therefore, there is a need to not use toxic solvents, or at least use less toxic solvents, so as to manufacture the web of fluoropolymers and / or the membrane obtained therefrom.
[0046] Furthermore, due to the risk of toxicity of nano-objects to humans, it is preferred that the web and / or the membranes obtained therefrom contain no or only very few fibers with a diameter less than or equal to 0.1 μm. It is therefore advisable to develop webs and / or membranes obtained therefrom whose electrostatic component of efficiency is improved so as to compensate for the loss of mechanical efficiency caused by the use of fibers with a diameter greater than 0.1 μm.
[0047] Purpose of the Invention
[0048] It is an object of the present invention to provide a web and / or membrane for filtering nano- and / or submicron aerosols that meets at least one of the above-mentioned needs.
[0049] It is an object of the present invention, at least according to certain embodiments, to provide webs and / or membranes suitable for air filtration whose fibers have improved ferroelectric properties.
[0050] It is another object of the present invention, at least according to certain embodiments, to provide webs and / or films that are suitable for filtering air intended to be breathed and therefore do not present any toxicological risk to human health.
[0051] Another object of the present invention is to propose, at least according to certain embodiments, webs and / or membranes intended for use as filter parts (components) of respiratory protection filter devices.
[0052] It is another object of the present invention, at least according to certain embodiments, to provide a web and / or membrane for filtering air which has an improved efficiency for a given pressure drop.
[0053] It is another object of the present invention, at least according to certain embodiments, to provide a web and / or membrane for filtering air that has a reduced pressure drop for a given efficiency.
[0054] It is another object of the present invention, at least according to certain embodiments, to provide webs and / or films for filtering air whose electrostatic efficiency is stable over time, particularly under varying conditions of humidity and temperature.
[0055] Another object of the present invention is to provide a web and / or membrane that is "durable" (in other words, has a low impact on the environment) at least according to certain embodiments. In particular, one object is to provide a web and / or membrane for air filtration that can be reused after cleaning and / or sterilization.
[0056] Other purposes directly derived from the above purposes, in particular:
[0057] - providing a method for producing a web and / or film;
[0058] - providing a filter comprising a web and / or a membrane, and any assembly on which the filter can be detachably or non-detachably mounted;
[0059] - Providing a method for washing and / or sterilizing webs and / or membranes, a filter resulting therefrom, and indeed even an assembly on which a filter is mounted, detachably or non-detachably. Summary of the invention
[0060] The present invention relates to a nonwoven porous and electrostatically charged web suitable for filtering nano and / or submicron aerosols. It comprises a plurality of fibers of a composition C1. Composition C1 comprises at least 50% by weight of at least one polymer P1 based on repeating units derived from vinylidene fluoride (VDF). The fibers of composition C1 have a crystallinity in one or more polar phases (preferentially only in β phase) of at least 65% by weight relative to their total weight.
[0061] The web according to the invention thus has an improved electrostatic efficiency due in particular to better ferroelectric properties.
[0062] According to certain embodiments, the fibers of composition C1 have a crystallinity in one or more polar phases (preferentially only in β phase) of at least 75% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight, or at least 96% by weight, or at least 97% by weight, or at least 98% by weight, or at least 99% by weight relative to their total weight.
[0063] According to certain embodiments, polymer P1 is selected from: a homopolymer of VDF; a copolymer having repeating units derived from VDF and at least one repeating unit derived from a monomer other than VDF, the other monomer being selected from the list consisting of vinyl fluoride (VF), tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorofluoroethylene (CFE), chlorodifluoroethylene, chlorotrifluoroethylene (CTFE), dichlorodifluoroethylene, trichlorofluoroethylene, hexafluoropropylene (HFP), trifluoropropylene, tetrafluoropropylene, chlorotrifluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, perfluoroethers, in particular perfluoroalkyl vinyl ethers, ethylene, acrylic monomers, methacrylic monomers and mixtures thereof; and mixtures of one or more homopolymers with one or more copolymers.
[0064] According to certain embodiments, polymer P1 is PVDF, P(VDF-HFP), P(VDF-TFE), P(VDF-TrFE) or a mixture thereof.
[0065] According to certain embodiments, the at least one polymer P1 is a mixture consisting of:
[0066] -PVDF,
[0067] - a copolymer selected from the group consisting of: P(VDF-HFP), P(VDF-TFE) and P(VDF-TrFE);
[0068] The weight ratio of PVDF relative to the copolymer is in the range of 1:99 to 99:1, preferably 10:90 to 90:10 and very preferably 25:75 to 75:25.
[0069] According to certain embodiments, polymer P1 represents at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 95%, or at least 97.5%, or at least 99.0% by weight of composition C1.
[0070] According to certain embodiments, composition C1 additionally comprises at least one polymer P1′ selected from the list consisting of poly(methyl methacrylate) (PMMA), poly(ethyl methacrylate) (PEMA), poly(methyl acrylate) (PMA), poly(ethyl acrylate) (PEA), poly(vinyl acetate) (PVAc), poly(vinyl ketone) (PVMK), thermoplastic polyurethane (TPU), thermoplastic starch, copolymers derived therefrom, and mixtures thereof.
[0071] According to certain embodiments, polymer P1 consists of PVDF and polymer P1′ consists of PMMA, the weight proportion of P1′ relative to the sum of the weights of polymers P1 and P1′ being 15% to 40%, preferentially 16% to 30% and very preferentially 17% to 23%.
[0072] According to certain embodiments, the web according to the invention consists of fibers of composition C1.
[0073] According to certain embodiments, the web has a 0.01 g / m 2 Up to 3g / m 2 , preferably 0.02g / m 2 Up to 1g / m 2 And very preferably 0.03g / m 2 Up to 0.5g / m 2 Weight per unit area.
[0074] According to certain embodiments, the web comprises less than 1%, preferentially less than 0.5% and more preferably less than 0.1% by number of fibers having a diameter strictly less than 100 nm.
[0075] The present invention also relates to a method for making a nonwoven porous and electrostatically charged web suitable for filtering nano and / or submicron aerosols, the web being according to the above-mentioned embodiments. The method comprises:
[0076] - providing at least one composition C1 comprising at least 50% by weight of at least one polymer P1 based on recurring units derived from VDF;
[0077] - Stage of forming a web by electrospinning composition C1.
[0078] The present invention additionally relates to a membrane suitable for filtering nano- and / or submicron aerosols, the membrane comprising:
[0079] - at least one web according to the above embodiments,
[0080] - A support layer supporting the web.
[0081] According to certain embodiments, the web within the film has a 0.01 g / m 2 Up to 3g / m 2 , preferably 0.02g / m 2 Up to 1g / m 2 And very preferably 0.03g / m 2 Up to 0.5g / m 2 Weight per unit area.
[0082] According to certain embodiments, the support layer is a nonwoven fiber set selected from the following: polyolefins, such as polyethylene (PE) or polypropylene (PP); polyesters, such as poly(ethylene terephthalate) (PET), poly(butylene terephthalate) (PBT) or poly(ethylene naphthalate) (PEN); polyamides or copolyamides, such as PA 11, PA 12, PA 6, PA6.6 or PA6.10; polyacrylonitrile (PAN); fluoropolymers, such as polyvinylidene fluoride (PVDF), fluorinated ethylene propylene (FEP) or polytetrafluoroethylene (PTFE), and mixtures thereof.
[0083] Finally, the invention relates to a method for washing / sterilizing a web according to the above embodiment or a film according to the above embodiment, which method comprises a heat treatment stage carried out at a temperature of 40°C to 90°C, preferentially 55°C to 85°C and very preferentially at a temperature of 65°C to 80°C.
[0084] Attached photos
[0085] [ Figure 1 ] Diagrammatic representation of the first device ("with needle") for electrospinning.
[0086] [ Figure 2 ] Diagrammatic representation of a second device for electrospinning ("without needle").
[0087] [ Figure 3 ]A membrane according to a first embodiment is diagrammatically represented.
[0088] [ Figure 4 ]A membrane according to a second embodiment is diagrammatically represented.
[0089] [ Figure 5 ]A membrane according to a third embodiment is diagrammatically represented.
[0090] [ Figure 6 ] Diagrammatically represents a filtering half mask comprising a membrane according to the invention.
[0091] [ Figure 7 ] Use a graphical method to express Figure 6 Possible configurations of filters for use in half masks. DETAILED DESCRIPTION
[0092] Web
[0093] The present invention relates to a nonwoven porous and electrostatically charged web suitable for filtering nano and / or submicron aerosols comprising a plurality of fibers of composition C1. Composition C1 comprises at least 50% by weight of at least one polymer P1 based on repeating units derived from VDF. The fibers of composition C1 have a crystallinity in one or more polar phases of at least 65% by weight relative to the total weight of the fibers.
[0094] Advantageously, the β phase is the main polar phase, in other words, it represents more than 50% by weight of the polar phase. Preferably, the β phase represents more than 80% or even more than 95% of the polar phase. In many cases, no γ and / or δ phases are detected, and the fiber is then considered to consist only of the β phase as the polar crystalline phase.
[0095] The β phase can be described by a sequence of all-trans (T) conformations along the polymer P1 chain. It is the most polar phase of the different possible phases that polymer P1 can adopt. Due to the presence of crystals in the β phase, polymer P1 is ferroelectric. It can be characterized by a hysteresis cycle of the electric displacement-applied electric field curve. Its coercive field at 25°C is typically greater than or equal to 40 V / μm. Its remanent polarization at 25°C is quite high and can typically reach greater than 40 mC / m 2 The value of .
[0096] Thus, the fibers of the web according to the invention, in particular the fibers of composition C1, are polarizable at relatively low coercive electric fields and exhibit a relatively high remanent polarization. The polarized fibers form permanent dipoles which are stable over time and to humidity (hydrophobicity). The polarized fibers are also temperature stable. This makes it possible to envisage methods for washing / sterilizing the web and / or the membranes obtained therefrom and for reusing these without significant losses in filtration efficiency.
[0097] The term "porous" is understood to mean that the web exhibits a set of empty spaces called pores. These pores are advantageously mainly open pores, in other words they can be connected together to form very fine channels. This makes it possible to make the web permeable to air and therefore any film obtained therefrom permeable to air.
[0098] The expression "electrostatically charged" is understood to mean that the web has a dipole charge and, if appropriate, a space charge.
[0099] The term "aerosol" is understood to mean a suspension of solid and / or liquid particles in a gas, in particular air, which exhibits a negligible fall rate. In air, at 25°C and 1015 hPa, this generally corresponds to particles with a size of less than about 100 μm. Aerosol particles (also called PM1) whose three external dimensions are less than 1 micron are described as submicron particles. Aerosol particles whose three external dimensions are less than 100 nanometers are described as nanoparticles.
[0100] Submicron or nanoaerosols include dust, mist and fog, as well as bioaerosols.
[0101] Dust, mist and dust clouds can be emitted by automobile traffic (incomplete combustion) or certain industrial activities (particles of chemical and / or thermal origin, or secondary particles formed during changes of phase, during chemical reactions or during gas condensation or liquid solidification phases).
[0102] Bioaerosols are aerosols containing live microorganisms (viruses, bacteria, molds and protozoa) or substances or products derived from these organisms (e.g. toxins, dead microorganisms or microbial fragments). Bioaerosols are ubiquitous in the environment and in the workplace. For example, they can originate from people, animals, plants and processed materials, or be generated by processes. In the case of the Covid 19 virus, the virus can be present in the air in the form of droplets projected by sneezing, coughing or splashing, or expelled by simple exhalation.
[0103] There are various indirect (eg by sampling, measuring concentration and microscopic observation) or direct (eg by electrical methods) measurement methods known to those skilled in the art in order to assess the concentration of particles in an aerosol and their size distribution.
[0104] Aerosols comprising NaCl particles with sizes ranging from 50 nm to 500 nm may advantageously be used to test the efficiency of the web or a film derived therefrom against bioaerosol type loadings.
[0105] The term "fiber" is understood to mean a filamentary element, which can generally be described by a diameter and a length.
[0106] The term "web of nonwoven fibers" is understood to mean a group of fibers obtained in particular by assembling fibers without weaving or knitting. According to EN ISO 9092, additional definitions are proposed by EDANA (European Disposal and Nonwoven Association), such as meaning a sheet made of directly or randomly oriented individual fibers bonded via friction, cohesion or adhesion.
[0107] The expression "crystallinity in the polar phase" is understood to mean the weight proportion of crystals in the polar phase relative to the total weight of the fiber. It can be obtained by multiplying the crystallinity of the fiber by the relative content of one or more polar crystalline phases within the crystalline phase.
[0108] The "degree of crystallinity" can be measured by wide angle X-ray scattering (WAXS). A spectrum of the scattered intensity as a function of the diffraction angle is thus obtained. When peaks are visible in the spectrum in addition to the amorphous halo, the spectrum makes it possible to identify the presence of crystals. In the spectrum, the area of the crystalline peak (expressed as CA) and the area of the amorphous halo (expressed as HA) can be measured. The weight proportion of the crystalline phase in the fiber is then calculated by the following ratio: (CA) / (CA+HA).
[0109] Alternatively, a method for quickly estimating crystallinity is to measure the melting enthalpy (ΔH) of the fiber by differential scanning calorimetry (DSC) in the first heating at a temperature gradient of 10°C / min. The weight proportion of the crystalline phase in the fiber is then estimated by the following ratio: (ΔHm+ΔHc) / ΔH100%, where ΔHm is the melting enthalpy, ΔHc is the enthalpy associated with the Curie phase transition, and ΔH100% is the theoretical enthalpy of a 100% crystalline sample.
[0110] The relative content of one or more polar crystalline phases in the crystalline phase corresponds in particular to the weight proportion of the β, γ and δ phases in the crystalline phase. It can be determined by various techniques, such as differential scanning calorimetry (DSC), X-ray spectroscopy or Fourier transform infrared spectroscopy (FTIR). Since the β phase is the most polar phase and / or the γ and δ phases may be present in small amounts or not at all, the relative content of one or more polar crystalline phases in the crystalline phase can usually be more or less approximately simplified to the content of the β phase only in the crystalline phase.
[0111] In addition, the prior art shows that the crystalline phases of the fibers obtained by electrospinning of PVDF are actually only α and β. In order to estimate the relative proportion F(β) of the β phase relative to the crystalline phase in the sample from the infrared spectrum of the sample, the relative intensity and absorption coefficient of the characteristic bands of the two phases are used. F(β) is given by the following formula:
[0112] [Formula 4]
[0113]
[0114] in:
[0115] x α and x β is the relative fraction of α and β phases in the crystalline phase,
[0116] A α is the absorbance of the characteristic band of the α phase, for example at 766 cm -1 Department,
[0117] A β is the absorbance of the characteristic band of the β phase, for example at 840 cm -1 Department,
[0118] K α is the absorption coefficient corresponding to the characteristic wavelength of the α phase (for 766 cm -1 , K α Estimated to be 6.1×10 4 ),
[0119] K β is the absorption coefficient corresponding to the characteristic wavelength of the β phase (for 840 cm-1, K β Estimated to be 7.7×10 4 ).
[0120] The term "copolymer" is understood to mean in a broad sense a polymer obtained by copolymerization of at least two types of chemically different monomers (called comonomers). Thus, in a broad sense, a copolymer is formed from at least two repeating units. It may, for example, be formed from two, three or four repeating units. In a strict sense, a copolymer is formed from exactly two repeating units, for example P(VDF-TrFE).
[0121] The term "mixture of polymers" is understood to mean a macroscopically homogeneous composition of polymers. The term encompasses mixtures of compatible polymers (in other words, miscible polymers) which exhibit a glass transition temperature between the glass transition temperatures of these polymers considered individually. The term also encompasses such compositions consisting of mutually immiscible phases dispersed on a micrometer scale.
[0122] The term "melting point" is understood to mean the temperature at which an at least partially crystalline polymer becomes a viscous liquid. The melting point can be measured by differential scanning calorimetry (DSC) according to standard NF EN ISO 11357-3:2018 using a heating rate of 10° C. / min in the second heating.
[0123] In this patent application, unless otherwise indicated, the singular forms "a", respectively "the" implicitly mean "at least one" and respectively "the at least one" (the latter formulation is not always used to alleviate certain wordings).
[0124] In all ranges listed in this patent application, the limits are included unless otherwise stated.
[0125] According to certain embodiments, the fibers of composition C1 have a crystallinity in one or more polar phases of at least 65% by weight and preferentially at least 75% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight, or at least 96% by weight, or at least 97% by weight, or at least 98% by weight, or at least 99% by weight, relative to their total weight.
[0126] Preferably, the fibers of composition C1 have a degree of crystallinity in the β phase of at least 65% by weight and preferentially at least 75% by weight, or at least 80% by weight, or at least 85% by weight, or at least 90% by weight, or at least 95% by weight, or at least 96% by weight, or at least 97% by weight, or at least 98% by weight, or at least 99% by weight, relative to their total weight.
[0127] Advantageously, the fibers of composition C1 have a degree of crystallinity of at least 60%, or at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%, or at least 90%, or at least 95%, or at least 99%.
[0128] Advantageously, the fibers of composition C1 have a relative content of one or more polar crystalline phases, in particular beta phase, of at least 85%, or at least 90%, or at least 95%, or at least 99%.
[0129] The crystallinity and / or relative content of one or more polar crystalline phases may be increased in various ways, as presented in the following embodiments.
[0130] According to certain embodiments, polymer P1 is selected from: a homopolymer of VDF; a copolymer having repeating units derived from VDF and at least one repeating unit derived from a monomer other than VDF, the other monomers being selected from the list consisting of vinyl fluoride (VF), tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorofluoroethylene (CFE), chlorodifluoroethylene, chlorotrifluoroethylene (CTFE), dichlorodifluoroethylene, trichlorofluoroethylene, hexafluoropropylene (HFP), trifluoropropylene, tetrafluoropropylene, chlorotrifluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, perfluoroethers, in particular perfluoroalkyl vinyl ethers, ethylene, acrylic monomers, methacrylic monomers and mixtures thereof; and mixtures of one or more of the foregoing homopolymers with one or more copolymers.
[0131] It should be clearly understood that all geometric isomers of the aforementioned fluorinated compounds are included in the above terms, such as: 1,1-chlorofluoroethylene (1,1-CFE), 1,2-chlorofluoroethylene (1,2-CFE), 1,2-dichloro-1,2-difluoroethylene, 1,1-dichloro-1,1-difluoroethylene and 1,1,2-trichloro-2-fluoroethylene, 3,3,3-trifluoropropene, 2-chloro-3,3,3-trifluoropropene (1233xf), 1-chloro-3,3,3-trifluoropropene (1233zd), 1,3,3,3-tetrafluoropropene, 2,3,3,3-tetrafluoropropene (or 1234yf), 3-chloro-2,3,3-trifluoropropene (or 1233yf), 3-chloro-3,3,3-trifluoropropene, 1,1,3,3,3-pentafluoropropene or 1,2,3,3,3-pentafluoropropene.
[0132] Among the perfluoroalkyl vinyl ethers, mention may be made of those of the general formula: R f -O-CF=CF2,R f is an alkyl group, preferably a C1 to C4 alkyl group, and for example methyl vinyl ether (MVE) or isopropyl vinyl ether (PVE).
[0133] Among the monomers of acrylic or methacrylic type, mention may be made of: acrylic acid, methacrylic acid, 2-(trifluoromethyl)acrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxyethylhexyl acrylate, hydroxyethylhexyl methacrylate and mixtures thereof.
[0134] In embodiments where P1 comprises a copolymer, the copolymer is advantageously a random copolymer.
[0135] In a preferred embodiment, polymer P1 is PVDF, P(VDF-HFP), P(VDF-TFE), P(VDF-TrFE) or a mixture thereof.
[0136] According to certain embodiments, the at least one polymer P1 consists of PVDF. This includes PVDF, in particular mixtures of PVDFs having different weight average molecular weights.
[0137] According to certain embodiments, the at least one polymer P1 consists of P(VDF-HFP), or P(VDF-TFE), or P(VDF-TrFE). This includes mixtures of copolymers such as P(VDF-TrFE) having different monomer ratios and / or different weight average molecular weights.
[0138] According to certain embodiments, the at least one polymer P1 is a mixture consisting of:
[0139] -PVDF,
[0140] - a copolymer selected from the group consisting of: P(VDF-HFP), P(VDF-TFE) and P(VDF-TrFE);
[0141] The weight ratio of PVDF to the copolymer is in the range of 1:99 to 99:1.
[0142] Preferably, the weight ratio of PVDF to the copolymer is 10:90 to 90:10. More preferably, the weight ratio of PVDF to the copolymer is 25:75 to 75:25.
[0143] P(VDF-HFP) advantageously has a molar proportion of recurring units originating from HFP of 15% to 35%.
[0144] P(VDF-TFE) advantageously has a molar proportion of repeating units derived from TFE of 8% to 30%, preferentially 15% to 28%, more preferentially 18% to 25% and very preferably 20% to 22%, relative to the total moles of units derived from VDF and TFE.
[0145] P(VDF-TrFE) advantageously has a molar proportion of repeating units derived from TrFE of 15% to 50%, preferentially 16% to 35%, more preferentially 17% to 32% and very preferably 18% to 28%, relative to the total moles of units derived from VDF and TrFE.
[0146] According to certain embodiments, polymer P1 has a melt flow index of 0.1 to 15 g / 10 min, preferentially 1 to 10 g / 10 min and more preferably 3 to 8 g / 10 min at 230° C. and a load of 12.5 kg, as measured according to standard ASTM D1238-13.
[0147] The composition C1 comprises at least 50% by weight of polymer P1 relative to the total weight of C1. A sufficiently high proportion of polymer P1 in C1 makes it possible to ensure that C1 is well crystallized, mainly in the ferroelectric form. According to certain embodiments, the composition C1 comprises at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 95%, or at least 97.5%, or at least 99.0% of polymer P1.
[0148] According to certain embodiments, the composition C1 may additionally comprise, in addition to the polymer P1, at least one polymer P1′. The polymer P1′ may in particular be chosen from the list consisting of poly(methyl methacrylate) (PMMA), poly(ethyl methacrylate) (PEMA), poly(methyl acrylate) (PMA), poly(ethyl acrylate) (PEA), poly(vinyl acetate) (PVAc), poly(vinyl ketone) (PVMK), thermoplastic polyurethanes (TPU), thermoplastic starches, copolymers derived therefrom, and mixtures thereof.
[0149] According to certain embodiments, the composition C1 comprises a polymer P1 and a polymer P1′, P1 consisting of PVDF and P1′ consisting of PMMA. Advantageously, the weight proportion of PMMA relative to the sum of the weights of PMMA and PVDF is advantageously between 15% and 40%, preferentially between 16% and 30% and even more preferentially between 17% and 23%. The addition of PMMA to PVDF in these proportions makes it possible to significantly increase the crystallinity in the β phase and to affect the crystallinity only to a lesser extent.
[0150] According to some embodiments, composition C1 may additionally contain a certain amount of additives. Examples of additives are, for example, additives with bactericidal or fungicidal effects. Composition C1 preferably contains less than 5% by weight, or less than 4% by weight, or less than 3% by weight, or less than 2% by weight, or less than 1% by weight of additives.
[0151] Advantageously, composition C1 does not contain conductive and / or thermally conductive additives such as carbon nanotubes, graphene or organosilicates. This is because such conductive additives may have a negative impact on the stability of the space charge, which may participate in the efficiency (electrostatic efficiency) of the membrane by induction. In particular, they tend to cause premature release of the fibers over time or in certain circumstances (e.g. washing and / or sterilization).
[0152] Likewise and advantageously, composition C1 does not comprise inorganic ferroelectric particles, such as ferrite particles or BaTiO 3 particles.
[0153] Likewise and advantageously, composition C1 does not comprise nanofillers, in other words fillers having at least one dimension less than or equal to 100 nm. This is because such fillers tend to represent a risk to human health through inhalation.
[0154] As an alternative to these embodiments, the composition C1 may consist solely of the polymer P1.
[0155] The web generally comprises at least 50% by weight of fibers of composition C1 relative to the total weight of the web. According to certain embodiments, the web comprises at least 60%, or at least 70%, or at least 80%, or at least 90%, or at least 95%, or at least 97.5%, or at least 99.0% of fibers of composition C1.
[0156] According to certain embodiments, the web may additionally comprise at least one composition C1′ different from composition C1. This other composition may be a composition consisting of at least 50% by weight of at least one other polymer than P1. This other composition may in particular be a composition consisting of at least 60% by weight, or at least 70% by weight, or at least 80% by weight, or at least 90% by weight, or at least 95% by weight of another polymer than P1. The other polymer than P1 may be one of the above-mentioned polymers P1′. The polymer than P1 may also be a polymer selected from the list consisting of: polyolefins, such as polyethylene or polypropylene, polyamides (PA 11; PA 12; PA 6; PA 6.6; PA6.10), poly(ethylene terephthalate) (PET), polyaryletherketone, polyethersulfone, polymethacrylate, polyacrylate, polyethylene oxide (PEO), polyethylene glycol (PEG), polystyrene (PS), polylactic acid (PLA), polyacrylic acid (PA), polyvinyl alcohol (PVA), polysulfone, polyacrylonitrile, polyurethane, polycaprolactone, polyimide, fluoropolymers such as PVDF, P(VDF-HFP), P(VDF-TFE), P(VDF-CFE), P(VDF-TrFE-CFE), P(VDF-TrFE-CTFE), polyvinyl fluoride (PVF), polychlorotrifluoroethylene (PCTFE), polytetrafluoroethylene (PTFE), poly(ethylene The invention relates to poly(ethylene-co-tetrafluoropropylene) (ETFE), poly(tetrafluoroethylene-co-perfluoropropyl ether) (PFA), poly(ethylene-co-chlorotrifluoroethylene) (E-CTFE), poly(tetrafluoroethylene-co-perfluoropropylene) (E-CPFP), polymethyl methacrylate (PMMA), PMMA copolymers such as poly(methyl methacrylate-co-ethyl acrylate) or PMMA-PS block copolymers, poly(ethyl methacrylate) (PEMA), poly(methyl acrylate) (PMA), poly(ethyl acrylate) (PEA), poly(vinyl acetate) (PVAc), poly(vinyl methyl ketone) (PVMK), thermoplastic polyurethane (TPU), thermoplastic starch, copolymers derived therefrom, and mixtures thereof.
[0157] As an alternative to these embodiments, the web may consist exclusively of fibers of composition C1.
[0158] The web fibers advantageously have a median diameter strictly greater than 100 nm.The diameter of the fibers and their distribution can be estimated by scanning electron microscopy (SEM), counting and analyzed by dedicated software.
[0159] According to certain embodiments, the fibers of the web have a median diameter greater than, or equal to, 150 nm, or greater than, or equal to, 200 nm, or greater than, or equal to, 250 nm.
[0160] According to certain embodiments, the median diameter of the fibers of the web is less than or equal to 1600 nm, or less than or equal to 1400 nm, or less than or equal to 1200 nm, or less than or equal to 1000 nm, or less than or equal to 800 nm, or less than or equal to 600 nm, or less than or equal to 550 nm, or less than or equal to 500 nm, or less than or equal to 450 nm.
[0161] According to certain embodiments, the web contains less than 1%, preferentially less than 0.5% and more preferably less than 0.1% by number of fibers having a diameter strictly less than 100 nm. These embodiments are particularly advantageous when the web is intended for use in respiratory protection filter devices due to the potential risks generated by the breathing of nano-objects (in other words, objects having at least one size dimension less than 100 nm).
[0162] According to certain embodiments, the median diameter of the fibers of the web may in particular be from 150 nm to 600 nm, preferentially from 200 nm to 500 nm and more preferentially from 250 nm to 450 nm.
[0163] According to certain embodiments, the web has a 0.01 g / m 2 Up to 3g / m 2 The weight per unit area (surface density) can be estimated by simply weighing a given surface area (e.g. 200 mm x 250 mm), preferably after placing in an oven to ensure that no residual solvent is present. The web preferably has a surface density of 0.02 g / m 2 Up to 1g / m 2 The weight per unit area is preferably 0.03 g / m 2 Up to 0.5g / m 2 Weight per unit area.
[0164] According to certain embodiments, the web has an average thickness of 0.1 μm to 100 μm. The average thickness can be estimated, for example, using a mechanical micrometer, an optical or laser sensor, or also by an optical microscope or by a scanning electron microscope (SEM). The web preferentially has an average thickness of 0.2 μm to 10 μm and more preferentially 0.3 μm to 0.8 μm.
[0165] According to certain embodiments, the web has a pressure drop for a nominal air flow of 95 l / min of less than or equal to 500 Pa, and / or a pressure drop for a nominal air flow of 30 l / min of less than or equal to 100 Pa (see standard EN149:2001+A1:2009). The web preferentially has a pressure drop for an air flow of 95 l / min of less than or equal to 350 Pa, preferentially less than or equal to 250 Pa, preferentially less than or equal to 100 Pa and very preferably less than or equal to 50 Pa. The web preferentially has a pressure drop for an air flow of 30 l / min of less than or equal to 75 Pa, preferentially less than or equal to 50 Pa and very preferably less than or equal to 25 Pa.
[0166] According to certain embodiments, the membrane has an efficiency of at least 75% for aerosols of atomized NaCl solution (particle size in the range of 50 nm to 500 nm). The membrane may particularly have an efficiency of at least 80%, or at least 85%, or at least 90%, or at least 94%, or at least 95%, or at least 96%, or at least 99%, or at least 99.90%, or at least 99.95%.
[0167] According to certain embodiments, the units produced from VDF in polymer P1 are produced at least partly from bio-based VDF. The term "bio-based" means "produced from biomass". This makes it possible to improve the ecological footprint of the film. Bio-based VDF may be characterized by a content of at least 1 atomic % of renewable carbon (in other words, carbon derived from natural sources of biomaterials or biomass), as defined by standard NF EN 16640. 14 The term "renewable carbon" indicates that the carbon is of natural origin and is derived from biological material (or biomass), as indicated below. According to certain embodiments, the biocarbon content may be greater than 5%, preferably greater than 10%, preferably greater than 25%, preferably greater than or equal to 33%, preferably greater than 50%, preferably greater than or equal to 66%, preferably greater than 75%, preferably greater than 90%, preferably greater than 95%, preferably greater than 98%, preferably greater than 99%, advantageously equal to 100%.
[0168] method
[0169] The method for manufacturing the web according to the invention comprises a stage of forming the web by electrospinning at least one composition C1.
[0170] Electrospinning is a well-known electrohydrodynamic method that makes it possible to manufacture small-sized polymer fibers, in particular fibers with diameters ranging from tens of nanometers to hundreds of nanometers. When a sufficiently high voltage is applied to a droplet of a polymer in a molten state or in a solution, the droplet becomes charged. The electrostatic repulsion then opposes the surface tension of the droplet, forcing the droplet to stretch until it forms a cone called a "Taylor cone". The charged jet is ejected from the tip of the Taylor cone and then accelerated by the electric field. The jet extends in the direction of the electric field and becomes thinner as it travels toward a grounded collector. The extension of the jet and its thinning are accompanied by the solidification of the polymer fiber. The fibers produced by the jet are collected directly on the collector at the end of its stroke, or advantageously on a substrate placed in front of the collector.
[0171] In particular, electrospinning can be "with needle" or "without needle", as described below by Figure 1 and 2 To make the explanation easier, then, for purely educational purposes and without any limitation, consider that the web consists of a single composition C1 , itself consisting of polymer P1 .
[0172] Figure 1 A schematic diagram of a "with needle" electrospinning facility commonly used in laboratories is presented. The facility 10 comprises a syringe 11 containing a solution 12 of a polymer P1. The syringe is usually equipped with a pump (not shown) making it possible to control the flow rate of the solution discharged therefrom. Facing the syringe is a grounded collector 14. A high voltage generator 13 between the syringe and the collector 14 makes it possible to generate an electric field. The filament 15 subjected to the electric field emerges from the syringe 11 and is preferably deposited on a substrate 16 different from the collector 14.
[0173] Figure 2 Schematic diagram showing a "needle-free" electrospinning facility, which is generally advantageous for obtaining a possible greater productivity (amount deposited in a given time) on a larger surface area. The facility 20 comprises an open bath 21 and a rotating electrode 22 immersed in the bath 21, the open bath 21 containing a polymer P1 in a fluid state (solution, molten state, etc.). The rotation speed of the electrode makes it possible to adjust the flow of the composition C1 ejected from the bath. Facing the bath 21 and the rotating electrode 22 is a grounded collector 24. A high-voltage generator 23 between the bath 21 / rotating electrode 22 and the collector 24 makes it possible to generate an electric field. The filaments 25 subjected to the electric field are ejected from the bath 21. They are preferably deposited on a substrate 26 different from the collector 24. In particular, the substrate 26 can be a rolling belt.
[0174] Several parameters of the process can be adjusted in order to obtain a web having advantageous properties, in particular having good filtration efficiency and / or low pressure drop and / or fewer fibers having a size less than 100 nm. The parameters are particularly adjusted in order to obtain fibers of a desired size having a substantially uniform appearance and minimizing the presence of beads.
[0175] The polymer P1 can be dissolved in various solvents or mixtures of solvents (“liquid vehicle”).
[0176] According to a first embodiment, the liquid vehicle does not contain dimethyl sulfoxide (DMSO) and comprises, consists essentially of, or consists of: at least 50% by weight of a 1 / 2 Up to 20MPa 1 / 2 A (first) liquid having a Hansen solubility parameter δp of and a boiling point greater than 100°C.
[0177] According to some alternative forms, the (first) liquid has a pressure of 15 MPa 1 / 2 Up to 20MPa 1 / 2 , preferably 15MPa 1 / 2 Up to 18MPa 1 / 2 The first liquid may consist in particular of gamma-butyrolactone, propylene carbonate or a mixture thereof. This alternative is particularly suitable when the fluoropolymer comprises or consists of PVDF.
[0178] According to another alternative, the (first) liquid has a pressure of 8 MPa. 1 / 2 Up to 15MPa 1 / 2 , preferably 10MPa 1 / 2 Up to 15MPa 1 / 2 The first liquid may be composed in particular of cyclopentanone, dimethyl phthalate, ethyl acetoacetate, triethyl phosphate, ethyl lactate and mixtures thereof. According to a first embodiment, the (first) liquid is selected from the list consisting of cyclopentanone, dimethyl phthalate, ethyl acetoacetate, triethyl phosphate, ethyl lactate, γ-butyrolactone, propylene carbonate and mixtures thereof. Preferably, the (first) liquid may be selected from the list consisting of cyclopentanone, dimethyl phthalate, ethyl acetoacetate, triethyl phosphate, ethyl lactate and mixtures thereof.
[0179] According to certain embodiments, the (first) liquid consists of cyclopentanone.
[0180] The liquid vehicle of this first embodiment may comprise at least one second liquid having a boiling point less than or equal to 100° C. The second liquid may in particular be chosen from the list consisting of acetone, ethyl acetate, 2-butanone, water and mixtures thereof. Advantageously, the second liquid consists of ethyl acetate or a mixture of ethyl acetate and water.
[0181] According to certain embodiments, the liquid vehicle comprises water, the water comprising up to 5 wt %, preferably up to 3 wt % of the liquid vehicle.
[0182] According to certain embodiments, the liquid vehicle consists of the at least one first liquid and the at least one second liquid.
[0183] According to certain embodiments, the weight ratio of the first liquid to the second liquid is 20:80 to 80:20 and preferably 50:50 to 75:25.
[0184] According to a second embodiment, the vehicle comprises: at least 15% by weight of dimethyl sulfoxide (DMSO) relative to the total weight of the liquid vehicle, and at least one second liquid having a pressure of 7 MPa. 1 / 2 Up to 15MPa 1 / 2 The Hansen solubility parameter δp and the boiling point are strictly greater than 100 °C.
[0185] According to certain embodiments, DMSO accounts for at least 20 wt%, preferentially at least 25 wt% and more preferentially at least 30 wt% of the total weight of the liquid vehicle.
[0186] According to certain embodiments, the second liquid comprises at least 10 weight percent of the total weight of the liquid vehicle.
[0187] According to certain embodiments, the second liquid has a pressure greater than or equal to 8 MPa. 1 / 2 , preferably greater than or equal to 9MPa 1 / 2 And most preferably greater than or equal to 10 MPa 1 / 2 Hansen solubility parameter δp.
[0188] According to certain embodiments, the second liquid is selected from the list consisting of cyclopentanone, dimethyl phthalate, ethyl acetoacetate, triethyl phosphate, ethyl lactate, and mixtures thereof.
[0189] According to certain embodiments, the second liquid consists of cyclopentanone.
[0190] According to certain embodiments, the weight ratio of DMSO to the second liquid is then advantageously between 40:60 and 60:40.
[0191] According to certain embodiments, the liquid vehicle consists of DMSO and the at least one second liquid. The weight ratio of DMSO to the second liquid is advantageously 40:60 to 60:40.
[0192] According to certain embodiments, the liquid vehicle comprises at least one third liquid having a boiling point less than or equal to 100° C. The third liquid advantageously represents 5% to 60% by weight relative to the total weight of the liquid vehicle.
[0193] According to certain embodiments, the third liquid is selected from the list consisting of acetone, ethyl acetate, 2-butanone, water, and mixtures thereof.
[0194] According to certain embodiments, the third liquid consists of ethyl acetate or a mixture of water and ethyl acetate.
[0195] According to certain embodiments, the third liquid comprises water, the water comprising up to 5 wt %, preferably up to 3 wt % of the liquid vehicle.
[0196] According to certain embodiments, the weight ratio of the sum of the weights of DMSO and the second liquid relative to the weight of the third liquid is advantageously between 20:80 and 80:20, preferentially between 40:60 and 60:40.
[0197] According to certain embodiments, the liquid vehicle is composed of DMSO, the at least one second liquid and the at least one third liquid. The weight ratio of the sum of the weights of DMSO and the second liquid relative to the weight of the third liquid is advantageously 20:80 to 80:20, preferably 40:60 to 60:40.
[0198] Advantageously, the following solvents are not used in the composition of the liquid vehicle to dissolve polymer P1 due to their CMR (carcinogenic, mutagenic or reprotoxic) risks: N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), tetrahydrofuran (THF), tetramethylurea, trimethyl phosphate and N-methyl-2-pyrrolidone.
[0199] According to certain embodiments, polymer P1 is dissolved in a DMSO / cyclopentanone / ethyl acetate liquid vehicle. Acetone and ethyl acetate in particular make it possible to make the mixture more volatile and they ensure good crystallization of the fibers.
[0200] The concentration of polymer P1 in one of the above-mentioned solvents or their mixture is between a minimum value and a maximum value, below or above which electrospinning no longer substantially forms filaments but beads. Generally speaking, the amount of polymer P1 in one of the above-mentioned solvents or their mixture is 3% to 30% by weight, preferentially 6% to 20% by weight and very preferably 9% to 12% by weight, based on the total weight of the solution.
[0201] Polymer P1 generally has a weight average molecular weight selected between a minimum and a maximum value. This is because too low a molecular weight results in the presence of undesirable beads during electrospinning. Too high a molecular weight tends to produce fibers with too large a diameter. Polymer P1 generally has a weight average molecular weight in the range of 100 000 g / mol to 2 000 000 g / mol. Preferably, it has a weight average molecular weight of 300 000 g / mol to 1 500 000 g / mol and extremely preferably 400 000 g / mol to 700 000 g / mol.
[0202] For a given molecular weight of polymer P1, in a given solvent or mixture of solvents, the concentration of P1 must be greater than the critical entanglement concentration.
[0203] The viscosity of the solution of polymer P1 measured by Brookfield viscometer at 25° C. is generally between 50 and 300 cP. Preferably, the viscosity of the solution is between 75 and 265 cP and very preferentially between 80 and 150 cP.
[0204] According to certain embodiments, the solution may contain additives that improve the processability of the filaments to be electrospun. In particular, the additives may be additives that enable certain electrohydrodynamic properties of the solution to be adjusted. The weight proportion of the additives generally does not exceed 5% of the total weight of the solution.
[0205] The additive may in particular be water. Water has the advantage of increasing the conductivity of the solution and evaporating during the electrospinning stage.
[0206] The additive may also be a salt. For example, NaCl and LiCl may be mentioned or also ammonium salts such as: TBAC (tetrabutylammonium chloride), TEAC (tetraethylammonium chloride) or TEAB (tetraethylammonium bromide). After the formation of the fibers by electrospinning, these salts may advantageously be at least partially removed by washing, in particular by washing with water.
[0207] As for Figure 1 and Figure 2 The equipment used in the facility shown in the figure can also be adjusted:
[0208] - voltage between the electrodes: the latter is generally adjustable to values between 5 kV and 40 kV; preferably, the voltage between the electrodes is chosen so as to be as low as possible in order to limit the energy consumption of the process and to prevent as much as possible any risks; 9 kV to 25 kV and very preferably 10 kV to 20 kV;
[0209] - The distance between the polymer spraying area and the substrate: this distance is usually adjusted to 5 cm to 30 cm, and preferably 10 cm to 20 cm;
[0210] - injection flow rate of polymer P1: depending on the type of equipment (syringe 11 or rotating electrode 22 immersed in bath 21), the flow rate is advantageously chosen to be as high as possible;
[0211] - Temperature of the medium in which the filaments of polymer P1 formed are intended to move: this directly influences the temperature at which the solvent evaporates from the solution; preferably, this temperature is close to ambient temperature. It may in particular be between 10°C and 80°C, preferentially between 20°C and 60°C and more preferentially between 25°C and 45°C.
[0212] - The relative humidity in which the filaments of polymer P1 formed are intended to move; preferentially, this humidity is between 20% and 60% at the temperature of the medium.
[0213] - or other specific conditions, such as forced air convection to promote solvent evaporation.
[0214] Webs formed by electrospinning do not necessarily require an additional poling stage, since the fibers are typically in a sufficiently polarized state after electrospinning due to the strong electric field applied.
[0215] The web formed by electrospinning may, after its formation, undergo an annealing phase at a temperature below the melting point of the polymer, then cool to ambient temperature (25° C.). This annealing phase makes it possible to optionally evaporate the residual solvent and optionally increase the crystallinity of P1 and thus enhance the ferroelectric properties. The annealing phase is usually followed by a poling phase, either by contact or by corona.
[0216] membrane
[0217] A web according to the present invention may alone be thick enough by itself to form a membrane suitable for filtering nano and / or submicron aerosols.
[0218] In contrast, the membrane for filtering nano- and / or submicron aerosols according to the present invention may comprise:
[0219] - at least one web according to the invention,
[0220] - a porous supporting layer supporting said at least one fiber web.
[0221] According to certain embodiments, the web has a 0.01 g / m 2 Up to 3g / m 2 The web preferably has a weight per unit area of 0.02 g / m 2 Up to 1g / m 2 The weight per unit area is preferably 0.03 g / m 2 Up to 0.5g / m 2 Weight per unit area.
[0222] According to certain embodiments, the web has an average thickness of 0.1 μm to 100 μm. The web preferentially has an average thickness of 0.2 μm to 10 μm and more preferentially 0.3 μm to 0.8 μm.
[0223] The support layer makes it possible, inter alia, to provide good mechanical strength of the membrane.The support layer may be a woven or nonwoven fiber assembly.
[0224] Advantageously, the support layer has a low pressure drop.
[0225] According to certain embodiments, particularly when the web is achieved by electrospinning, the support layer may be a substrate onto which the web has been electrospun.
[0226] According to certain embodiments, the support layer may be a nonwoven thermoplastic fiber group. The support layer may in particular be a nonwoven fiber group selected from the following: polyolefins, such as polyethylene (PE) or polypropylene (PP); polyesters, such as poly(ethylene terephthalate) (PET), poly(butylene terephthalate) ester (PBT) or poly(ethylene naphthalate) ester (PEN); polyamides or copolyamides, such as PA 11, PA 12, PA6, PA 6.6 or PA 6.10; polyacrylonitrile (PAN); fluoropolymers, such as polyvinylidene fluoride (PVDF), fluorinated ethylene propylene (FEP) or polytetrafluoroethylene (PTFE), and mixtures thereof.
[0227] According to certain embodiments, the support layer is easily obtained by a meltblowing process or by a spunbonding process. The meltblowing process generally makes it possible to obtain fibers with a diameter ranging from 0.5 μm to 10 μm. The spunbonding process generally makes it possible to obtain fibers with a diameter ranging from 10 μm to 50 μm and is generally cheaper to carry out than the meltblowing process.
[0228] According to certain embodiments, the support layer has a 5 g / m 2 Up to 100g / m 2 , preferably 10g / m 2 Up to 50g / m 2 And extremely preferably 15g / m 2 Up to 40g / m 2 Weight per unit area.
[0229] According to a specific embodiment, the membrane comprises one or more webs according to the invention, for example consisting essentially of or consisting of PVDF fibers, or fibers consisting of a mixture of PVDF and P(VDF-HFP) or P(VDF-TFE) or P(VDF-TrFE), or also fibers consisting of a mixture of PVDF and PMMA. The one or more webs are obtained by electrospinning and have a density of 0.02 g / m 2 Up to 1g / m2 The substrate can be in particular PVDF, PP or also PET, which is obtained by meltblowing and has a weight per unit area of 10 g / m 2 Up to 50g / m 2 Weight per unit area.
[0230] Figure 3 A multilayer film 30 consisting of a support layer 31 and a single web 32 is shown.
[0231] Figure 4 A multilayer film 40 is shown consisting of a support layer 41 covered on each side with a web 42 and a web 43, respectively ("sandwiched"). The webs 42 and 43 may be identical or, conversely, different, in particular showing a different composition and / or a different weight per unit area and / or a different thickness. For example, the web 42 may have the same chemical composition as the web 43, but show a different weight per unit area and / or a different thickness.
[0232] Figure 5 A multilayer film 50 according to the invention is shown, which consists of a support layer 51 covered successively with three webs 52, 53 and 54. The webs 52, 53 and 54 can be identical or, on the contrary, different, in particular showing different compositions and / or different weights per unit area and / or different thicknesses. Device for filtering nano- and / or submicron aerosols from air
[0233] The web and / or membrane according to the present invention may constitute a filter and / or form part of a multilayer assembly constituting a filter, thereby constituting or forming part of a device for filtering nano- and / or submicron aerosols from the air.
[0234] According to certain embodiments, the device for filtering nano- and / or submicron aerosols from air is a respiratory protection filter device.
[0235] There are many different designs of respiratory protection apparatus known to those skilled in the art (INERIS Publication, ED6106, Respiratory protection apparatuses, August 2019 – ISBN 978-2-7389-2503-9).
[0236] The respiratory protection device can be in particular a filtering half mask, a half mask containing a filter or a mask containing a filter. The respiratory protection device can be free-ventilating or assisted-ventilating.
[0237] According to a preferred embodiment of the invention, the respiratory protective device is free-ventilating. The respiratory protective device may in particular be a filtering half mask as described below. The respiratory device may in particular be a medical mask (see standard EN 14683) or a FFP type mask (see standard EN 149).
[0238] According to certain embodiments, the filter comprising the web and / or membrane allows filtering only nano- and / or submicron aerosols from the air.
[0239] According to certain embodiments, the filter comprising the web and / or membrane is a combined filter, enabling filtration of nano and / or submicron aerosols and anti-toxic gas filtration.
[0240] Figure 6 A filtering half mask 60 is shown, comprising a filter 61, means for securing the filter to the face (in particular a nose strip 62, an elastic strap 63), and an exhalation valve 64 (optional in certain configurations).
[0241] refer to Figure 7 , the filter 61 is composed of three layers: two outer layers 72 and 73 , one adapted and intended to come into contact with the user's face, the other adapted and intended to come into contact with the external environment, and an intermediate layer consisting of the membrane 30 .
[0242] Washing / sterilization method
[0243] The webs and / or films according to the invention can advantageously be washed and / or sterilized so as to be reusable. They can be washed / sterilized preferably at least 5 times, preferably at least 10 times, more preferably at least 20 times, more preferably at least 30 times and very preferably at least 50 times.
[0244] Washing can especially be carried out with water, preferably hot water.
[0245] Sterilization methods include:
[0246] - chemical treatment with chemicals in liquid or vapor form;
[0247] -UV-C treatment;
[0248] - heat treatment; and
[0249] - Combinations of treatments.
[0250] Examples of chemical treatments are treatment with hydrogen peroxide (HPV / HPVP), VHP, HPGP, iHP and aHP.
[0251] UV-C treatment is a treatment with radiation having a wavelength in the range of 100 to 280 nm. This makes it possible to sterilize the web and / or film. Advantageously, the UV-C treatment is carried out by means of a lamp with a radiation peak in the range of 230 to 270 nm, in particular around 254 nm. The treatment is generally applied at a dose of 1 J / cm to 120 J / cm, preferentially 1 J / cm to 50 J / cm.
[0252] The heat treatment may be carried out for a sufficient period of time, preferably less than or equal to 30 minutes and more preferably less than or equal to 15 minutes, at a temperature generally greater than or equal to 40° C. It may be carried out in particular at a temperature greater than or equal to 50° C., or greater than or equal to 60° C., or greater than or equal to 70° C., or greater than or equal to 80° C.
[0253] Heat can be "dry" heat or "wet" heat (greater than 50% humidity).
[0254] Apparatus capable of carrying out this treatment are in particular heating cabinets, water baths, autoclaves or ovens.
[0255] The treatment is selected and adjusted according to various constraints such as the nature and strength of other materials other than the web, which must be subjected to the treatment, use in a hospital or domestic environment, etc. Therefore, users of washable and / or sterilizable respiratory protective equipment are advised to be fully informed by carefully reading the manufacturer's instructions and the recommendations of official standards and / or health agencies, which may have to be changed over time. To the best of our knowledge, at the time of writing this patent application, domestic ovens and microwave ovens for domestic use are not part of the washing / sterilization methods recommended by the main official standards and / or health agencies for masks for domestic use, in particular due to the lack of existing data and the potential risk of biological / chemical contamination of ovens. In its advice of 25 March 2020 (revised on 21 April 2020), ANSM [French National Agency for the Safety of Medicines and Health Products] recommends that fabric masks for non-hygienic purposes, such as those provided in the context of the COVID pandemic, be treated at home as follows: i) machine washing with a detergent suitable for fabrics, using a cycle containing a plateau period of at least 30 minutes at 60°C, and ii) mechanical drying or conventional drying, followed in both cases by steam ironing at a temperature compatible with the composition of the mask.
Claims
1. A nonwoven web obtained by electrospinning, suitable for filtering nano- and / or submicron aerosols, comprising a plurality of fibers of composition C1, The composition C1 comprises at least 50% by weight of at least one polymer P1 based on repeating units derived from vinylidene fluoride (VDF), said fibers of composition C1 having a degree of crystallinity in the polar phase of at least 65% by weight relative to their total weight; wherein polymer P1 has a weight average molecular weight in the range of 400 000 g / mol to 700 000 g / mol; The nonwoven web contains less than 0.1% by number of fibers having a diameter strictly less than 100 nm. 2 . The web of claim 1 , wherein the crystallinity is crystallinity in only the β phase. 3 . The web according to claim 1 , wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 75% by weight, relative to their total weight. The web of claim 3 , wherein the crystallinity is in the β phase only. 5 . The web according to claim 3 , wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 80% by weight relative to their total weight. 6 . The web according to claim 5 , wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 85% by weight relative to their total weight. 7 . The web according to claim 6 , wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 90% by weight relative to their total weight.
8. The web according to claim 7, wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 95% by weight relative to their total weight.
9. The web according to claim 8, wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 96% by weight relative to their total weight. 10 . The web according to claim 9 , wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 97% by weight relative to their total weight. 11 . The web according to claim 10 , wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 98% by weight relative to their total weight. 12 . The web according to claim 11 , wherein the fibers of composition C1 have a degree of crystallinity in the polar phase of at least 99% by weight relative to their total weight.
13. The web according to any one of claims 1 to 12, wherein the polymer P1 is selected from: homopolymers of VDF; copolymers having repeating units derived from VDF and at least one repeating unit derived from a monomer other than VDF, the other monomers being selected from the list consisting of vinyl fluoride (VF), tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorofluoroethylene (CFE), chlorodifluoroethylene, chlorotrifluoroethylene (CTFE), dichlorodifluoroethylene, trichlorofluoroethylene, hexafluoropropylene (HFP), trifluoropropylene, tetrafluoropropylene, chlorotrifluoropropylene, hexafluoroisobutylene, perfluorobutylethylene, pentafluoropropylene, perfluoroethers, ethylene, acrylic monomers, methacrylic monomers and mixtures thereof; and mixtures of homopolymers and copolymers.
14. The web of claim 13, wherein the perfluoroether is selected from perfluoroalkyl vinyl ethers.
15. The web according to any one of claims 1 to 12, wherein the polymer P1 is PVDF, P(VDF-HFP), P(VDF-TFE), P(VDF-TrFE) or a mixture thereof.
16. The web according to any one of claims 1 to 12, wherein the at least one polymer P1 is a mixture consisting of: -PVDF, - a copolymer selected from the group consisting of: P(VDF-HFP), P(VDF-TFE) and P(VDF-TrFE); The weight ratio of PVDF to the copolymer is in the range of 1:99 to 99:
1.
17. The web of claim 16, wherein the weight ratio of PVDF to the copolymer is in the range of 10:90 to 90:
10.
18. The web of claim 16, wherein the weight ratio of PVDF to the copolymer is in the range of 25:75 to 75:
25.
19. The web of any one of claims 1 to 12, wherein the polymer P1 comprises at least 60% by weight of the composition C1.
20. The web of claim 19, wherein the polymer P1 comprises at least 70% by weight of the composition C1.
21. The web of claim 20, wherein the polymer P1 comprises at least 80% by weight of the composition C1.
22. The web of claim 21, wherein the polymer P1 comprises at least 90% by weight of the composition C1.
23. The web of claim 22, wherein the polymer P1 comprises at least 95% by weight of the composition C1.
24. The web of claim 23, wherein the polymer P1 comprises at least 97.5% by weight of the composition C1.
25. The web of claim 24, wherein the polymer P1 comprises at least 99.0% by weight of the composition C1.
26. The web according to any one of claims 1 to 12, wherein the composition C1 additionally comprises at least one polymer P1′ selected from the list consisting of poly(methyl methacrylate) (PMMA), poly(ethyl methacrylate) (PEMA), poly(methyl acrylate) (PMA), poly(ethyl acrylate) (PEA), poly(vinyl acetate) (PVAc), poly(vinyl ketone) (PVMK), thermoplastic polyurethane (TPU), thermoplastic starch, copolymers derived therefrom, and mixtures thereof.
27. The web according to claim 26, wherein the polymer P1 consists of PVDF and the polymer P1' consists of PMMA, the weight proportion of P1' relative to the sum of the weights of the polymers P1 and P1' being 15% to 40%.
28. The web according to claim 27, wherein the weight proportion of P1' relative to the sum of the weights of the polymers P1 and P1' is 16% to 30%.
29. The web according to claim 28, wherein the weight proportion of P1' relative to the sum of the weights of the polymers P1 and P1' is 17% to 23%.
30. The web according to any one of claims 1 to 12, consisting of fibers of composition C1.
31. The web of any one of claims 1 to 12 having a g / m 2 Up to 3g / m 2 Weight per unit area.
32. The web of claim 31 having a g / m 2 Up to 1g / m 2 Weight per unit area.
33. The web of claim 32 having a g / m 2 Up to 0.5g / m 2 Weight per unit area.
34. The web of any one of claims 1 to 12, comprising no solvent from the list consisting of: N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), tetrahydrofuran (THF), tetramethylurea, trimethyl phosphate, and N-methyl-2-pyrrolidone.
35. A membrane suitable for filtering nano and / or submicron aerosols, comprising: - at least one web according to any one of claims 1 to 34, - A support layer supporting the web.
36. The membrane of claim 35, wherein the support layer is a nonwoven fiber selected from the group consisting of: polyolefins; polyesters; polyamides or copolyamides; polyacrylonitrile (PAN); fluoropolymers, and mixtures thereof.
37. The film of claim 36, wherein the polyolefin is selected from polyethylene (PE) or polypropylene (PP).
38. The film of claim 36, wherein the polyester is selected from poly(ethylene terephthalate) (PET), poly(butylene terephthalate) (PBT), or poly(ethylene naphthalate) (PEN).
39. The membrane of claim 36, wherein the polyamide or copolyamide is selected from PA 11, PA 12, PA 6, PA 6.6 or PA 6.
10.
40. The membrane of claim 36, wherein the fluoropolymer is selected from polyvinylidene fluoride (PVDF), fluorinated ethylene propylene (FEP), or polytetrafluoroethylene (PTFE).
41. Method for washing / sterilizing a web according to any one of claims 1 to 34 or a film according to any one of claims 35 to 40, comprising a heat treatment stage carried out at a temperature of 40 to 90°C.
42. Process according to claim 41, comprising a heat treatment phase carried out at a temperature ranging from 55°C to 85°C.
43. The method according to claim 42, comprising a heat treatment phase carried out at a temperature ranging from 65°C to 80°C.
Citation Information
Patent Citations
Electrostatically-charged Nanofiber Media and Fabrication Method Thereof
US20190314746A1
Anti-virus mask
CN105688349A